MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KECERDASAN EMOSIONAL SISWA - Manaf, Sofwan; Rokimin, Rokimin (STKIP Pesisir Selatan, 2025)
Emotional Intelligence (Emotional Quotient, EQ) of students is a crucial factor that influences academic achievement, personal well-being, and social abilities in school, family, and society. This study aims to identify effective leadership management strategies implemented by the school principal to enhance the emotional intelligence of Grade VI students at MTs Darunnajah Jakarta. The research method used is a qualitative approach with a library research technique, based on theoretical analysis and literature. Data was collected through observations, interviews, documentation, and an analysis of the decisions made by the school administration. This can be observed from the changes in students' character, such as becoming more polite, disciplined, optimistic, and always remembering Allah. Therefore, MTs Darunnajah Jakarta has successfully maintained an A accreditation, reflecting the high quality of the school. The novelty of this study lies in the systematic application of leadership management theory in enhancing students' emotional intelligence, integrated with the principles of Islamic education. This research contributes to the development of school leadership management and the improvement of students' emotional intelligence as a foundation for character formation and academic achievement.